1987
DOI: 10.1161/01.str.18.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Directional C-W Doppler sonography in the diagnosis of basilar artery disease.

Abstract: Using directional continuous-wave Doppler sonography of the vertebral arteries, we have investigated 1,540 patients during the past 5 years. On the basis of unilateral and bilateral retrograde brachial angiograms in the same patients (a total of 1,989 angiograms) we have developed sonographic criteria for demonstrating a significant increase in the peripheral resistance of both distal vertebral arteries and/or the basilar artery. All 11 cases of basilar artery stenosis of at least 60% reduction in lumen diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The basilar artery was examined from a median suboccipital probe position at an insonation depth of 7.5 cm or more. 26,29,30,32,33 Analysis of Ultrasound Findings Maximal systolic and diastolic and time mean BFV were measured in each vessel. Pulsatility index (PI) was calculated according to the following formula: PI=(Systolic BFV -Diastolic BFV)/Mean BFV.…”
Section: Transcranial Doppler Examinationmentioning
confidence: 99%
“…The basilar artery was examined from a median suboccipital probe position at an insonation depth of 7.5 cm or more. 26,29,30,32,33 Analysis of Ultrasound Findings Maximal systolic and diastolic and time mean BFV were measured in each vessel. Pulsatility index (PI) was calculated according to the following formula: PI=(Systolic BFV -Diastolic BFV)/Mean BFV.…”
Section: Transcranial Doppler Examinationmentioning
confidence: 99%
“…In many cases there is a delay between dissection, signalled by neck and head pain, and the symptoms and signs caused by the cerebral lesion. Recognition of the pain and its appropriate interpretation therefore is the clue to early diagnosis which may be confirmed noninvasively by ultra-sound, 12,13,[14][15][16][17][18] In this report we present a prospective analysis of features and time course of neck pain and headache in 14 patients with VAD proven by angiography or magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 97%
“…Color-flow Doppler and duplex scanning have been studied as methods of evaluating vertebrobasilar disease [36][37][38][39][40][41][42], and though some have suggested that such studies may help in the determination of the occlusion site, this technique has not yet been standardized or validated.…”
Section: Recommendationmentioning
confidence: 99%